2006
DOI: 10.1002/dvdy.21051
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial expression patterns of heparan sulfate sulfotransferases in zebrafish: III. 2‐O‐sulfotransferase and C5‐epimerases

Abstract: Heparan sulfate (HS) is an unbranched chain of repetitive disaccharides, which specifically binds ligands when attached to the cell surface or secreted extracellularly. HS chains contain sulfated domains, termed the HS fine structure, which give HS specific binding affinities for extracellular ligands. HS 2-Osulfotransferase (2-OST) catalyzes the transfer of sulfate groups to the 2-O position of uronic acid residues of HS. We report here the characterization and developmental expression patterns of 2-OST in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In zebrafish, all ndst enzyme isoforms were expressed in varying brain regions throughout the development, with the ndst3 isoform expressed predominantly in the central nervous system. Previous studies of the other HS modifying enzymes also revealed highly specific spatial and temporal expression patterns of enzyme paralogs during Danio rerio development [12, 4246] indicating a need of strict regulation of HS structure in developmental processes. Differences in enzyme kinetics and substrate preferences of the different isoforms could possibly result in variable HS structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebrafish, all ndst enzyme isoforms were expressed in varying brain regions throughout the development, with the ndst3 isoform expressed predominantly in the central nervous system. Previous studies of the other HS modifying enzymes also revealed highly specific spatial and temporal expression patterns of enzyme paralogs during Danio rerio development [12, 4246] indicating a need of strict regulation of HS structure in developmental processes. Differences in enzyme kinetics and substrate preferences of the different isoforms could possibly result in variable HS structures.…”
Section: Discussionmentioning
confidence: 99%
“…To this date, eight 3-OSTs [9] and four 6-OSTs [1012] have been characterized in zebrafish. One 2- O -sulfotransferase and two zebrafish C5-epimerase genes, Glce-A and Glce-B, have also been reported [13, 14]. Despite the key role that NDST enzymes play in HS biosynthesis, only one previous morpholino (MO) knockdown study of an ndst homolog in zebrafish has been published.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there is a growing literature on the use of ZF as a model to study viral diseases including herpes simplex virus [1116]. Interestingly ZF is known to express multiple isoforms of heparan sulfate modifying enzyme 3- O -sulfotransferase (3- O ST) [1719]. Cadwallader and Yost [18] reported in vivo characterization of eight 3- O ST family members in ZF with seven genes showing homology to known 3- O ST genes in mouse and humans.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Sdc2 might be the primary HSPG functioning in DFCs/KV, and that other HSPG core proteins provide redundant regulation of tbx16 in other tissues. Alternatively, cell-specific HS-GAG modifications, through families of sulfotransferases with tissue-and development-specific expression patterns (Cadwallader and Yost, 2006a;Cadwallader and Yost, 2006b;Cadwallader and Yost, 2007), might enable Sdc2 to regulate tbx16 expression in DFCs/KV, but not in other tissues.…”
Section: Sdc2 Regulates Lr Development Through Multiple Lineage-specimentioning
confidence: 99%